Taxonomy building tools : an investigative study. - Sia, Chin Lan. (2008)
This research project is to do an investigative study on taxonomy building tools. Ten taxonomy software were selected and evaluated by through identifying the main features of the taxonomy tools, identifying the value-added features of the taxonomy tools and doing a comparison on the similarities and differences of the ten taxonomy tools.